2021
DOI: 10.1371/journal.pone.0243709
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with admission to intensive care units in COVID-19 patients in Lyon-France

Abstract: Introduction A new respiratory virus, SARS-CoV-2, has emerged and spread worldwide since late 2019. This study aims at analysing clinical presentation on admission and the determinants associated with admission in intensive care units (ICUs) in hospitalized COVID-19 patients. Patients and methods In this prospective hospital-based study, socio-demographic, clinical and biological characteristics, on admission, of adult COVID-19 hospitalized patients presenting from the community for their first admission wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
24
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 25 publications
11
24
2
1
Order By: Relevance
“…The median age of patients with COVID-19 was similar to that found in other studies (56.0-72.0 years) [11][12][13][14][15][16][17], with a predominance of males, as also identified in most studies (51.9-62.0%) [11][12][13][15][16][17][18], except in a cohort of patients in the USA where a higher proportion of females (55.9%) was described [14]. Regarding these sociodemographic variables, some studies have found that males have a higher risk of complications [14,19,20] and death [14,18,20]; those findings were not identified in this report, but our results are consistent with those described in other studies [15,21,22]. It was observed that as age increased, patients had a higher probability of dying, consistent with a large number of international publications [14,17,[21][22][23][24] and local studies [11,25], probably due to a higher disease burden [10].…”
Section: Plos Onesupporting
confidence: 88%
See 2 more Smart Citations
“…The median age of patients with COVID-19 was similar to that found in other studies (56.0-72.0 years) [11][12][13][14][15][16][17], with a predominance of males, as also identified in most studies (51.9-62.0%) [11][12][13][15][16][17][18], except in a cohort of patients in the USA where a higher proportion of females (55.9%) was described [14]. Regarding these sociodemographic variables, some studies have found that males have a higher risk of complications [14,19,20] and death [14,18,20]; those findings were not identified in this report, but our results are consistent with those described in other studies [15,21,22]. It was observed that as age increased, patients had a higher probability of dying, consistent with a large number of international publications [14,17,[21][22][23][24] and local studies [11,25], probably due to a higher disease burden [10].…”
Section: Plos Onesupporting
confidence: 88%
“…The clinical manifestations most described in the literature have been cough, fever and dyspnea [11,14,15,17,22,23], as found in this analysis. With respect to the NEWS 2 score, which involves different clinical parameters, this report showed that a higher score was associated with a greater probability of requiring ICU care, a result that is consistent with a study conducted in Colombia (Bogota ´), where the score was associated with a greater risk of disease severity (for each 1-point increase, (HR:1.15; 95%CI:1.03-1.28) [11].…”
Section: Plos Onesupporting
confidence: 68%
See 1 more Smart Citation
“…The NOSO-COR study is an international observational, prospective, multicentric study carried out in 13 French hospitals and hospitals affiliated with the GABRIEL network [10] in order to estimate the prevalence and incidence of SARS-CoV-2 infection and to assess the associated characteristics among healthcare workers and patients. Our previous results, based on 417 patients, showed that in COVID-19 patients, age as well as delay between symptom onset and hospital admission were both associated with ICU admission [11].…”
Section: Introductionmentioning
confidence: 90%
“…Finally, no centenarian was transferred to intensive care units (ICUs) in our study. As reported in our previous publication [ 8 ], rapid management, thanks to earlier presentation at hospital, and/or shortage of intensive care resources in the context of a pandemic could impact the decisions about ICU admission in this population. Considering the potential increase in the number of centenarians in the future, lessons learned from the COVID-19 pandemic should be kept in mind for better management of this population in case of a new emerging infectious disease.…”
mentioning
confidence: 98%